2014
DOI: 10.1363/4017614
|View full text |Cite
|
Sign up to set email alerts
|

Young Women’s Access to and Use of Contraceptives: The Role of Providers’ Restrictions in Urban Senegal

Abstract: Family planning services were introduced in Senegal in the early 1960s at the private Blue Cross Clinic in Dakar, but it was only in 1981 that the government developed an administrative structure capable of directing a national program and began to provide information, education and counseling support and family planning services. Factors contributing to unmet need for family planning in developing countries include lack of contraceptive knowledge; poor quality of and access to family planning services; method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 11 publications
4
110
1
Order By: Relevance
“…Our findings on provider imposed eligibility criteria based on age, parity, marital status and consent are similar to studies from Ghana [9], Senegal [8], and Tanzania [7]. As shown in those three contexts, providers in urban Kenya are imposing barriers to use, particularly for younger or unmarried women.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings on provider imposed eligibility criteria based on age, parity, marital status and consent are similar to studies from Ghana [9], Senegal [8], and Tanzania [7]. As shown in those three contexts, providers in urban Kenya are imposing barriers to use, particularly for younger or unmarried women.…”
Section: Discussionsupporting
confidence: 83%
“…Speizer et al (2000) conducted a study among Tanzanian service providers and found that many providers restricted access to modern methods such as pills, injectables, and intrauterine devices (IUCDs) based on age, with a minimum age restriction of 14-15 years and a maximum age restriction of 43-44 years [7]. Results from a recent (2014) study in urban Senegal found that approximately half of providers impose minimum age restrictions with a median minimum age of 18 years [8]. In a study conducted in Ghana, Stanback and Twum-Baah (2001) found that providers restricted the provision of injectables to those 30 years and older [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Interestingly, provider attitudes were cited as one of the main barriers to access, yet only nine informants had ever visited a SRH service delivery point, so this barrier may not be based only on experiences, but also on perceptions. These are compounded by the restricting social and gender norms (especially regarding behavioural expectations for women) and lack of access to information about where they can access SRH services.…”
Section: Discussionmentioning
confidence: 99%
“…The use of combined injectables showed no increased risk; however, the only study that addressed this method was conducted more than a decade ago. It is worth mentioning that use of injectable contraceptives has increased in recent years, becoming the hormonal method most used by women in some countries (31)(32) . Likewise, the use of vaginal ring and contraceptive patch has increased as they became more easily available and users became more aware of them (33) .…”
Section: Discussionmentioning
confidence: 99%